Severe Infliximab-Induced Alopecia and Scalp Psoriasis in a Woman with Crohn's Disease: Dramatic Improvement after Drug Discontinuation and Treatment with Adjuvant Systemic and Topical Therapies. Issue 4 (December 2016) - Udkoff, Jeremy; Cohen, Philip
Abstract Scalp psoriasis with alopecia is a rare cutaneous reaction to tumor necrosis factor alpha antagonists. This reaction often reverses with discontinuation of the offending drug and initiation of topical treatments; however, irreversible hair loss may occur if a scarring alopecia develops. We describe a woman with Crohn's disease who developed scalp psoriasis and alopecia secondary to infliximab. She had a remarkable recovery after discontinuation of infliximab and treatment with oral minocycline and topical therapy: mineral oil under occlusion, betamethasone lotion, and sequential coal tar, salicylic acid, and ketoconazole shampoos each day. The patient's alopecia completely resolved within 4 months of initiating this treatment regimen. In summary, early diagnosis of alopecia secondary to tumor necrosis factor alpha antagonist therapy is crucial in preventing diffuse alopecia and scalp psoriasis. In addition to discontinuing the offending agent, initiating aggressive adjuvant treatment with an oral antibiotic, topical therapies, or both, should be considered to reverse tumor necrosis factor alpha antagonist-induced alopecia and/or scalp psoriasis.